2012
DOI: 10.1039/c2cc32964f
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed aerobic oxidation and cleavage/formation of C–S bond: a novel synthesis of aryl methyl sulfones from aryl halides and DMSO

Abstract: With atmospheric oxygen as the oxidant, a novel copper(I)-catalyzed synthesis of aryl methyl sulfones from aryl halides and widely available DMSO is described. The procedure tolerates aryl halides with various functional groups (such as methoxy, acetyl, chloro, fluoro and nitro groups), which could afford aryl methyl sulfones in moderate to high yields. The copper-catalyzed aerobic oxidation and the cleavage/formation of C-S bond are the key steps for this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…However, the troublesome compatibility of the stoichiometric amount of oxidant and harsh reaction conditions in these processes might be the major challenges. [4] During our search for more selective aerobic oxidative transformations, [5] we reasoned that a copper/carbene species could be a versatile precursor in such conversions. Herein, we would like to present an example of ketoneto-alkyne (via hydrazones) transformation by selective deprotonation in the presence of O 2 .…”
mentioning
confidence: 99%
“…However, the troublesome compatibility of the stoichiometric amount of oxidant and harsh reaction conditions in these processes might be the major challenges. [4] During our search for more selective aerobic oxidative transformations, [5] we reasoned that a copper/carbene species could be a versatile precursor in such conversions. Herein, we would like to present an example of ketoneto-alkyne (via hydrazones) transformation by selective deprotonation in the presence of O 2 .…”
mentioning
confidence: 99%
“…287 Aryl methyl sulfones 44 are obtained via CuO 2 -catalyzed oxidation and cleavage/formation of carbon-sulfur bond from aryl halides and DMSO (Scheme 32). 288 After first oxidation of DMSO to the corresponding sulfone, the reactive complex 43 has been suggested to be involved in the formation of sulfone 44. Sulfoxides undergo photochemical oxidation to sulfones in variable yield.…”
Section: Oxidation Of Sulfoxides To Sulfones By Miscellaneous Methodsmentioning
confidence: 99%
“…23 Ionic liquids (ILs) are a fascinating class of solvent that have been widely embraced by the catalysis community as a method for immobilization of catalysts under homogeneous, liquid-liquid biphasic and liquid-solid (SILP) biphasic conditions. 24 Recent relevant examples include an efficient protocol for the oxidation of sulfides to sulfones catalyzed by V 2 O 5 in [C 12 mim] [HSO 4 ], 25 highly selective sulfoxidation of sulfides to sulfoxides catalysed by the bifunctional IL combination [SO 3 HC 3 py][TiF 6 ]/[C 4 py] [BF 4 ], 26 a selective catalyst-free oxidation of sulfides to sulfoxides that is faster in ionic liquid than conventional solvents, 27 and, most recently, heterogeneous selective oxidation of sulfides catalysed by ionic liquid-based polyoxometalates 28 or tungstate-based poly(ionic)liquid entrapped magnetic nanoparticles. 29 While good conversions and high selectivities have been obtained In IL media, surprisingly few recycle studies have been reported.…”
Section: Introductionmentioning
confidence: 99%